RETRACTED: Perspective drilling methods, holes - Fayzimatov Baxodir; Khusanov Yunusali; Fayzimatov Shuxrat; Sattorov Abdusalom; Omonov Abdukaxxor; Nazarova Gulsanam; Usmonov Mamur (E3S Web of Conferences)
See the retraction notice E3S Web of Conferences 538, 00001 (2024), https://doi.org/10.1051/e3sconf/202453800001